Changes in tissue factor and activated factor XII following an acute myocardial infarction were uninfluenced by high doses of n-3 polyunsaturated fatty acids - Grundt, Heidi; Hetland, Øyvind; Nilsen, Dennis W.T. (Thrombosis and Haemostasis, 2003)
Few data exist on the effects of n-3 polyunsaturated fatty acids (PUFAs) on the initiators and endstage products of coagulation following an acute myocardial infarction (MI).We assessed the long-term effects of n-3 PUFAs on postinfarct variations of tissue factor (TF), activated factor XII (FXIIa) and fibrin monomer (FM), and expected additional statin treatment to modify thrombogenicity.Acute MI patients (n = 300) were randomly allocated to a high dose of n-3 PUFAs or corn oil for at least one year.Plasma concentrations of TF, FXIIa and FM were unaffected by n-3 PUFAs as compared to corn oil, and were uninfluenced by additional statin treatment in subgroup analyses. TF decreased (p = 0.0001), while FXIIa increased during the first 6 weeks (p = 0.001). FM remained essentially unchanged during the entire observation period.In conclusion, TF, FXIIa and FM were unaffected by long-term treatment with high- dosed n-3 PUFAs and by additional statin treatment.
Keywords: Tissue factor; activated factor XII; fibrin monomer; n-3 PUFAs; myocardial infarction